ANALISA PENGENDALIAN PERSEDIAAN BAHAN BAKU STEEL SCRAP PADA INDUSTRI PENGECORAN LOGAM - Solihin Abdillah; Ibnu Bari Taqi; Muchammad Fauzi (Universitas Widyatama, 2020)
Steel scrap is waste product from the results of industrial production processes at manufacture industries for automatic components. Although according to manufacture companies, steel scrap considered as garbage or waste material, except for upstream companies such as steel casting manufacture steel scrap considered as raw materials. To fullfill production needs, steel scrap play an important role for the continuity of production companies engaged in metal casting. The problem that occasionally occurs in metal casting companies is sometimes the cost of raw materials increases due to lack of steel scrap. The needs for steel scrap itself is influenced by production demands that have high fluctuation and tend to be uncertain. Uncertainty inventory method expected to provide an optimal profit picture. The purpose of this study is to determine the number of purchases of the most economical raw materials within one year and predict purchases in the following years. The location of this research was conducted at a metal casting company located in Karawang, West Java.